Role and Therapeutic Potential of the Pro-Longevity Factor FOXO and Its Regulators in Neurodegenerative Disease - Neri, Christian (Frontiers in Pharmacology, 2012)
Studies in simple model organisms have yielded crucial insights into the genetic and molecular aspects of longevity. FOXO, which is most notable for its association with longevity, and its upstream regulators such as sirtuins have received particular attention in translational research because these genes modulate cell survival in several models of neurodegenerative diseases. There is a large amount of knowledge on the pathways that regulate FOXO activity and genes that may be regulated by FOXO. However, for the same reason that the FOXO network is a complex stress response system, its therapeutic potential to develop disease-modifying strategies requires further examination. Although the FOXO network contains druggable genes such as sirtuins and AMPK, whether they should be activated or inhibited and whether protection against the early or late phases of neuronal cell decline might require opposite therapeutic strategies remains unclear. Additionally, the mode of action of small compound molecules believed to act on FOXO network targets happened to be questionned. This review recapitulates essential facts and questions about the promises of of FOXO and its interactors in neurodegenerative disease.